Is empirical antibiotic treatment required in COVID-19 patients? What lessons have we learnt over the past 1 year? - Saseedharan, Sanjith (International Journal of Research in Medical Sciences, 2022)
Background: Secondary bacterial infections manifest during or after a viral infection(s) and can lead to negative outcomes and sometimes fatal clinical complications. The choice for an empiric antibiotic therapy requires a broad spectrum of activity against pathogens including beta-lactamase producing pathogens. Ceftriaxone+sulbactam+disodium EDTA is one of the antibiotic combinations used to prevent secondary infections. The objective was to evaluate rate of secondary bacterial infections in patients receiving empirical antibiotic therapy through retrospective analysis of data from a tertiary care center. Methods: A single center, retrospective analysis of data from hospital of COVID-19 patients treated in the ICU or wards was conducted. Patients who received empirical antibiotic therapy including ceftriaxone+sulbactam+disodium EDTA were included in the study. Results: 99 patients (mena age 75±9.89 years) were included in the retrospective analysis. Diabetes and hypertension were the most common comorbidities in the patients. The total WBC count was raised (12.36±9.01). All the biological markers were raised. 45% patients had abnormalities in chest X-ray. The mean CT severity index was 13.81±5.64. Bacterial superinfection was observed only in 1 patient. Conclusions: Bacterial co infections and secondary bacterial infections are a major risk factor for adverse COVID-19 outcomes. The use of appropriate prophylactic antibiotics such as ceftriaxone+sulbactam+disodium EDTA has significantly reduced the prevalence of secondary bacterial infections in patients with severe COVID.